Smart specialisation benchmarking and assessment: pilot study on wind energy - Jiménez-Navarro, Juan-Pablo; Uihlein, Andreas (My University, 2017)
This work was carried out in the framework of the Smart Specialisation Platform on Energy (S3PEnergy). It aims at supporting the implementation of regional smart specialisation strategies and the optimal and effective uptake of cohesion funds in the energy area. This report aims to foster cooperation amongst regions with common interest in a particular energy theme, which allows mutual learning amongst regions. Consequently, the objective of this work is to provide and test a methodology to identify similarities within a group of regions with a particular interest in wind energy. This analysis facilitates the identification of leading regions and regions with structural similarities and recommends potential partnerships amongst them.
Política de acceso abierto del editor: https://data.jrc.ec.europa.eu/licence/com_reuse
Keywords: Energía eólica; Regional innovation; S3P; Smart Specialisation Platform; Wind Energy